Avaliação de genótipos de azevém diplóide e tetraplóide com manejos distintos de cortes visando duplo propósito - Tonetto, Cleber José (2009)
The objective of the work was to evaluate the chemical composition and production of dry matter and seed in five genotypes of ryegrass subjected to different number of cuts, with emphasis on growing dual purpose. The experimental delineation was adopted in blocks at random, with four repetitions and the treatments were distributed in factorial scheme 5x5 (genotypes x number of cuts). Was used five genotypes: Comum , São Gabriel , Estanzuela 284 , Avance and Titán and five cut number (one, two, up to five cuts). It was observed (P <0.05) significance interaction with genotype x number of cut for all the variables studied. The increase in the number of cuts ordered greater accumulation of total dry matter (leaves and stems), but lower seed production for all genotypes studied. The response of the chemical composition of dry matter varied depending on the genotype and the number of cuts. The increase in the number of cuts promoted lower crude protein content of leaf and stem for all genotypes studied. The highest level of neutral detergent fiber of stem genotype was found in São Gabriel and Comum . The genotypes showed quadratic answer to the contents of neutral detergent fiber of leaves, and the lowest level was observed when there were up to three cuts. Aiming the dual-purpose, you must choose from two to three cuts, given a good production of dry matter to animals but also promoting a seed production satisfactory.